(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
Self inflicted burn injuries are infrequent but very much distressing. It is a result of social, environmental and individual factors. Self-inflicted burns are usually an outcome of mental illness, and acute phase schizophrenia is considered as one of the major precipitating factor. The aim of this study was to find out and summarize the existing findings of different studies regarding mental illness as a contributor to suicide and/or intentional self inflicted injury. Literature review of some of previous studies from journals and databases were performed. Electronic database (Medline) was searched and twenty four studies were found to be related to the present objective. Among the 10 studies were randomly selected. The studies ranged from 1991-2005. The literature review suggested that quite a good number of incidents of self inflicted burns are committed by people having mental disorder. Among the self inflicted burns patient, the males were seen to be higher in number in most of the studies provided information. The range of the age was 14 to 90 years collectively. And among them a significant number of people are suffering from schizophrenia. Depression, substance abuse, personality disorder, psychosis were among the other mental health illness contributing to the incidence of self inflicting burns injury. Specific attention should be given in this aspect as for the vulnerable group depends heavily on their care givers. Since a number of inter-related risk factors may be involved, solving the problem from a new perspective-the safety promotion perspective should be initiated. DOI: http://dx.doi.org/10.3329/jdnmch.v18i1.12242 J. Dhaka National Med. Coll. Hos. 2012; 18 (01): 49-57